1994
DOI: 10.1126/science.8310296
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Molecular Chaperone Action

Abstract: Molecular chaperones of the Hsp70 type transiently sequester unfolded segments of proteins and promote their correct folding. Target peptides were labeled with an environmentally sensitive fluorophore so that their binding to the molecular chaperone DnaK of Escherichia coli could be followed in real time. The two-step process was characterized by relaxation times of 27 seconds and 200 seconds with 2 microM DnaK and 0.1 microM ligand at 25 degrees C. In the presence of adenosine triphosphate, the formation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
437
1
5

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 453 publications
(477 citation statements)
references
References 15 publications
34
437
1
5
Order By: Relevance
“…4 B-D), the extended conformation of rhodanese disappears with a rate constant of (2.5 ± 0.4) 10 −3 s −1 (Table S1). This rate is in a similar range as previously determined off-rates for substrates from ADP-bound DnaK (38,47,48). After reaching equilibrium, the transfer efficiency histograms are indistinguishable from those of the DnaJ-rhodanese complex, suggesting complete dissociation of DnaK (compare Fig.…”
Section: Dynamics Of Complex Formation From Microfluidicsupporting
confidence: 86%
“…4 B-D), the extended conformation of rhodanese disappears with a rate constant of (2.5 ± 0.4) 10 −3 s −1 (Table S1). This rate is in a similar range as previously determined off-rates for substrates from ADP-bound DnaK (38,47,48). After reaching equilibrium, the transfer efficiency histograms are indistinguishable from those of the DnaJ-rhodanese complex, suggesting complete dissociation of DnaK (compare Fig.…”
Section: Dynamics Of Complex Formation From Microfluidicsupporting
confidence: 86%
“…Earlier studies showed that DnaJ deletion mutants that lack the complete zinc binding region are still capable of interacting with substrate proteins such as 32 (18). This suggested that the low affinity binding site might be located in the C terminus of DnaJ.…”
Section: Discussionmentioning
confidence: 99%
“…5B). This is due to the negligible affinity of DnaK-ATP complexes to substrate proteins (32,33). The presence of both DnaJ and DnaK in a 0.5:10:1 molar ratio of DnaJ:DnaK:luciferase, however, completely suppressed luciferase aggregation (compare Fig.…”
Section: Fig 4 the Dnaj Zinc Center II Is Important For The Functiomentioning
confidence: 99%
“…1A) (Schmid et al 1994;Gisler et al 1998;Mayer et al 2000b). Spontaneous transition between the two states is extremely slow but is stimulated synergistically by substrates and DnaJ (Karzai and McMacken 1996;Laufen et al 1999).…”
Section: Introductionmentioning
confidence: 99%